Imbalan Mengajar dalam Perspektif Islam: Studi Hadis Nabi Muhammad SAW dan Pandangan Ulama - Al Qosam, Arvaddin Hamasy (Perkumpulan Sarjana Pendidikan Islam Indonesia (PSPII) Wilayah Kalimantan Barat, 2023)
The writing of this article is to discuss the theory of receiving rewards or teaching wages for teachers or instructors from the hadith perspective. The purpose of this study is to explain how the concept of teaching rewards for an educator is related to Islamic religious theory. The research method used is library research and uses a qualitative approach. The data sources used in this study are divided into two, namely primary and secondary sources. The primary data source is in the form of the hadith of the prophet regarding teaching rewards, while the secondary sources are obtained from several data from scientific journals, papers, previous research results, and books related to this research. The article writing results are, (1) there is a hadith by Bukhari from Ibn Abbas which explains that it is permissible to receive wages for teaching results. (2) According to Al-Ghazali, receiving rewards from students is only permissible in the realm of teaching non-religious sciences, and it is permissible to receive rewards from educational institutions but only to meet needs, not to enrich oneself. (3) According to Al-Zarnuji, it is permissible to receive rewards from students, whether in religious or non-religious knowledge. (4) while Ibn Jama’ah argues that it is permissible to receive rewards from students, and suggests educational institutions to meet the necessary of teachers. Abstrak: Penulisan artikel ini adalah membahas tentang teori menerima imbalan atau upah mengajar bagi para guru atau pengajar dalam sudut pandang hadis. Adapaun tujuan dari penelitian ini ialah untuk menjelaskan terkait bagaiamana konsep imbalan mengajar bagi seorang pendidik menurut teori agama Islam. Metode penelitian yang digunakan bersifat studi pustaka (library research) dan menggunakan pendekatan kualitatif. Sumber data yang digunakan pada penelitian terbagi menjadi dua, yakni sumber primer dan sekunder. Sumber data primer berupa hadis nabi tentang imbalan mengajar, sedangkan sumber sekunder diperoleh dari data beberapa jurnal ilmiah, karya tulis , hasil penelitian sebelumnya dan buku-buku yang terkait dengan penelitian ini. Hasil penulisan artikel ini adalah, (1) terdapat hadis oleh bukhari dari Ibnu Abbas yang menjelaskan terkait bolehnya menerima upah dari hasil mengajar. (2) Menurut Al-Ghazali, menerima imbalan dari murid hanya diperbolehkan pada ranah mengajar ilmu non keagamaan, dan diperbolehkan menerima dari lembaga pendidikan tetapi hanya sebatas untuk memenuhi kebutuhan, bukan untuk memperkaya diri. (3) Menurut Al-Zarnuji memperbolehkan menerima imbalan dari murid, baik dalam ilmu agama atau non agama. (4) sedangkan Ibn Jama’ah berpendapat memperbolehkan menerima imbalan dari murid, dan menyarankan kepada lembaga pendidikan untuk memenuhi kebutuhan guru. Kata Kunci: Imbalan, Islam, Mengajar